Selective area epitaxy of high quality Wurtzite-InAs heterostructure on InGaAs nanopillars at indium-rich region using MOCVD. (15th November 2021) - Anandan, Deepak; Yu, Hung Wei; Chang, Edward Yi; Singh, Sankalp Kumar; Nagarajan, Venkatesan; Lee, Ching Ting; Dee, Chang Fu; Ueda, Daisuke
Abstract: We report synthesis of Au-free selective area epitaxy of InGaAs/InAs heterostructure nanopillars on patterned Si (111) substrate by metal-organic chemical vapor deposition. Effect of trimethylindium supply on InGaAs/InAs heterostructure nanopillars morphology and crystal structure is studied. Transmission electron microscopy images reveal subtle and consistent differences at the growth front of the InGaAs nanopillars for different indium-flow rate fraction. Notably, the nanopillar growth front exhibits zincblende-InAs cap for the low indium-flow rate fraction, whereas a sharp wurtzite-InAs segment is found at high indium-flow rate fraction. Nanopillar geometry profile fitting attributes that the wurtzite-InAs segment formation is ascribed to indium adatom diffusion on the sidewall surface along with direct impingement of indium growth species on the top facet of the nanopillar. Additionally, X-ray photoelectron spectroscopy confirms that indium segregation is more pronounced at the sidewall of the nanopillar under arsenic-limited region. Highlights: Au-free SAE-InGaAs/InAs heterostructure (HS) nanopillars are grown on Si substrate. Influence of TMIn flow on InAs HS morphology is investigated. Axial WZ-InAs HS is realized when the Indium-flow rate fraction is high. Sidewall diffusion and direct impingement dominate InAs HS morphology.